Optimization Cassamore (Cassava – Moringa Mix) Extrusion Process as A Feed Substitute for Corn: Optimasi Proses Ekstrusi Cassamore (Cassava Moringa) Berbahan Baku Singkong Sebagai Pakan Pengganti Jagung - Risyahadi, Sazli Tutur; Sukria, Heri Ahmad; Afrilia, Hanifah (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
As a corn substitute, cassamore (Cassava – Moringa Mix) is an innovative local feed ingredient based on cassava with a mixture of palm kernel meal, cassava leaf flour and moringa extract processed by extrusion that can destroy antinutrients, improve nutrient content and digestibility. This study aimed to optimize the temperature and water content of the hydrothermal extrusion process, as well as to analyze the effect of extrusion on the physical and chemical characteristics of Cassamore as a corn substitution. The method used is response surface methodology in the statistical application of design expert 13 with extrusion temperature factors of 100, 110, 120 (oC) and moisture content of 16, 18, 20 (%). Further research was carried out for the physical and chemical properties of Cassamore using a complete randomized design (CRD). The results showed that the water absorption index value is significant (p<0.05) with the optimal value located at 100 °C and 20% moisture content, while the water solubility index value is not significant. The values of bulk density, tapped density, and angle of repose on Cassamore after being extruded were smaller than those before being extruded. The bulk density and tapped density values for Cassamore were below corn, while Cassamore's angle of respose was above the corn. Cassamore's specific gravity value after extruding under corn. Chemical properties (Ash, crude protein, crude fat, crude fiber) decreased after extrusion, but NFE increased after extrusion. It is concluded that Cassamore has a potency to replace corn. Key words: cassava, corn, extrusion, moringa oleifera, palm kernel meal